Ethno-Religious Violence and Peacebuilding Approaches in Jos, Plateau State, Nigeria - Gambo, Joseph; Mashal, Jemlak Michael Mashal; Nanlop, Bentu-Harami Rachel Nanlop; Yakubu, Melissa Daria Joshua Yakubu; Nanlung, Paul Satur Nanlung (African Journal of Stability and Development (AJSD), 2025)
Identity, a cornerstone of human existence, often manifests through affiliations such as religion and ethnicity. In Nigeria, the instrumentalisation of these identities for specific gains has frequently fuelled violent conflicts. Nigeria's history is replete with instances of ethno-religious and political violence, resulting in significant losses of life and property. This research examines the historical roots and expressions of ethno-religious violence in Jos, Plateau State, Nigeria. Specifically, it investigates the 2004 Plateau State Conference, a deliberate effort to address and mitigate this violence. The articulated objectives of the conference are analysed. To understand governmental responses to the ethno-religious tensions, the study explores the emergence and functions of the Plateau Peace Building Agency (PPBA), established to foster grassroots engagement and maintain peace. Furthermore, the research considers the contributions of faith-based organisations in offering religious perspectives on conflict resolution. The study also addresses the role of commissions of inquiry and the deployment of security forces in response to these violent episodes. Findings indicate that the indigene-settler dichotomy remains a primary driver of conflict in Jos. The theoretical framework of Peacebuilding Theory is applied to analyse the ethno-religious contestations within Jos. This study relies on secondary data, utilising online resources to access relevant scholarly books, journals, and other materials, all of which are appropriately cited. As a means of addressing ethno-religious violence, the study recommends that religious and ethnic organisations actively cultivate opportunities for increased intergroup interaction and understanding.